The Influence of Employee Participation on Jamsostek and Pension Fund to Productivity in PT Cement Gresik (Persero) - Yunus, Eddy (Jurnal Aplikasi Manajemen, 2012)
Abstract: The purpose in this study: (1) To know the magnitude of the influence of Social Security and Pension Fund partially on the productivity of the production employees of PT. Semen Gresik, (2) To know the magnitude of the influence of Social Security and pension fund simultaneously on the productivity of the production employees of PT. Semen Gresik. Data analysis techniques used to solve the problem in this study are qualitative and quantitative analysis using multiple linear regression analysis. The analysis is known that Social Security and pension fund has a positive influence on worker productivity. If Jamsostek variable and pension fund increased, it will affect the increase of worker productivity.Keywords: social security, pensions, productivity, worker